2023
DOI: 10.3390/ijms24021399
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Modification of Microfibrous Polycaprolactone by pCMV-VEGF165 Plasmid Promotes Local Vascular Growth after Implantation in Rats

Abstract: Insufficient vascular growth in the area of artificial-material implantation contributes to ischemia, fibrosis, the development of bacterial infections, and tissue necrosis around the graft. The purpose of this study was to evaluate angiogenesis after implantation of polycaprolactone microfiber scaffolds modified by a pCMV-VEGF165-plasmid in rats. Influence of vascularization on scaffold degradation was also examined. We investigated flat microfibrous scaffolds obtained by electrospinning polycaprolactone with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Klabukov et al explored flat microfibrous scaffolds obtained by electrospinning polycaprolactone with the incorporation of the pCMV-VEGF-165 plasmid into the microfibres at concentrations of 0.005 ng of plasmid per 1 mg of polycaprolactone (0.005 ng/mg) (LCGroup) and 0.05 ng/mg (HCGroup) [85]. The results demonstrated that pCMV-VEGF165 plasmid functionalisation of polycaprolactone led to better vascularisation 33 days after implantation; however, vessel growth did not appear to be correlated with scaffold degradation rate [85].…”
Section: Vascular Tementioning
confidence: 99%
“…Klabukov et al explored flat microfibrous scaffolds obtained by electrospinning polycaprolactone with the incorporation of the pCMV-VEGF-165 plasmid into the microfibres at concentrations of 0.005 ng of plasmid per 1 mg of polycaprolactone (0.005 ng/mg) (LCGroup) and 0.05 ng/mg (HCGroup) [85]. The results demonstrated that pCMV-VEGF165 plasmid functionalisation of polycaprolactone led to better vascularisation 33 days after implantation; however, vessel growth did not appear to be correlated with scaffold degradation rate [85].…”
Section: Vascular Tementioning
confidence: 99%
“…The design of smart scaffolds for the creation of tissue-engineered grafts requires not only new materials and methods for their modification [ 120 ], but also quantitative models for the assessment of their physiological relevance [ 121 , 122 ]. Therefore, the design of tissue-engineered grafts that fulfill clinical requirements remains a grand challenge for the creation of physiologically relevant tissue-engineered organs and tissues.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…On the other hand, coaxial electrospinning definitely varies from the emulsion-based method as it produces higher-mechanical-strength fibers. In tissue engineering, coaxial-produced nanofibers revealed better cell attachment and proliferation due to a core-sheath nanostructure [61]. However, both coaxial and emulsion electrospinning form nanofibers having an outer sheath and inner core.…”
Section: Electrospinning Technique For Nanofibersmentioning
confidence: 99%